L'exploration de controverses comme argumentation socio-cognitivo-émotionelle : débattre de la gestion de l'eau potable de façon constructive - Claire Polo (Université de Provence, 2022)
At the crossroads of education and linguistics, my argument is based on a corpus of ten videotaped debates organized in 2011 and 2012 in Mexico, the US and France. The studied innovative pedagogical activity brings teenagers to reason about what would determine access to drinking water in the future. In this paper, I focus on the quality of student-student interactions in small groups, showing that engaging in a cognitive exploration of the controversy relies on socio-cognitivo-emotional argumentation. On the basis of previous literature, I propose 5 indicators of the quality of group talk and specify how it relates on the one hand with the deepening of the space of debate at the group scale and, on the other hand, with the strengthening of arguments, at the individual scale. I also show how exploratory talk requires appropriate, both anticipatory and reactive, emotional regulation. A case study illustrates how these analytical categories apply to authentic student discourse.